Inclusive Prosperity: Bridging Finance and Community for SME Empowerment - Ramadhan, Yudi (Golden Ratio of Community Services and Dedication, 2024)
This study investigates the synergistic impact of bridging finance and community support mechanisms on Small and Medium Enterprises (SMEs) empowerment and inclusive prosperity. Through a comprehensive literature review, the study aims to elucidate the multifaceted nature of bridging finance and community-based initiatives, highlighting their significance in fostering SME growth and resilience. The research employs a qualitative approach, drawing insights from existing theoretical frameworks and empirical studies to analyze the interplay between financial and non-financial factors in driving SME empowerment. Findings reveal that bridging finance initiatives, including working capital loans, trade finance facilities, and venture capital investments, play a pivotal role in addressing SMEs' short-term funding needs and enhancing their market competitiveness. Additionally, community support mechanisms, such as mentoring, networking, and capacity-building programs, contribute to SME empowerment by facilitating knowledge exchange, collaboration, and resource-sharing within local communities. The integration of bridging finance and community support offers a holistic approach to SME development, enabling stakeholders to create an enabling environment that supports SME growth, innovation, and socio-economic inclusion. The study underscores the importance of continued research and collaboration in advancing our understanding of the mechanisms driving inclusive prosperity and informing evidence-based policy and practice interventions aimed at promoting SME development and sustainable economic growth.